(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses the role of family and marriage in the context of striving for gender equality in society. Also, the problems of introducing gender equality in relation to the institution of the family and their traditional alternatives were comparatively studied.